STUDI ANALISIS KINERJA POMPA AIR DENGAN MENGGUNAKAN SUMBER LISTRIK DARI PANEL SURYA - sulanjari; Joko Setiyono (Magister Teknik Mesin Universitas Pancasila, 2020)
In areas of Indonesia that are crossed by the equator, the availability of sunlight is very potential and all day. Therefore in the case of application as a source of electrical energy to drive a water pump with a set of solar cell panels it is very possible. The level or intensity of sunlight illumination from sunrise to sunset is very different. The intensity of sunlight is certainly very influential on the ability of solar cell panels to convert them into electrical energy.Surely it will have an impact on the performance of the solar water pump system. Thus in this study will test the performance and analyze the performance of water pumps driven using electricity from solar cell panels. To achieve this goal measurements of the power generated by solar panels starting from 12:00 WIB to 16:00 WIB for three days (three repetitions) were carried out in the open field programmed in the Mechanical Engineering Study of Pamulang University. Data collection is done by measuring the intensity of sunlight, battery input power, and water discharge.The solar panel used is 100wp capacity, the highest solar panel power produced is 25.3W at 12:00 WIB with an intensity value of 114700 lux, while the lowest power value is 13.83 W at 16:00 WIB with an intensity value of 47301 lux. Charging a battery with a capacity of 12V / 35A from a minimum voltage to full using a 100 wp solar panel takes an average of 4 hours 28 minutes. The use of a battery with a capacity of 12V / 35A from full to minimal voltage conditions to drive an AC water pump takes an average of 1 hour 48 minutes and produces an average water volume of 1855.33 liters. Or the resulting average water discharge is 17.08 liters / minute.